Cecal and ilial intubation rates in colonoscopy: Comparative study: Cecal and ilial intubation rates in colonoscopy: Comparative study - Muslim, Osamah Tahir; Al-Obaidi, Hasan Osamah Al-Obaidi (Journal of Population Therapeutics and Clinical Pharmacology, 2021)
Background: Colonoscopy is the procedure of choice for both the diagnosis and treatment of large intestine and distal ilium in patients complaining of bowel symptoms, anemia resulting from malabsorption, radiographic colon abnormalities, screening for colorectal carcinoma, after polypectomy and cancer resection surveillance, ulcerative colitis surveillance, and those with suspicion of neoplastic masses. Inspectionof the whole colonic and distal portion of terminal ilial mucosa is usually feasible during colonoscopy. Quality examination of the large bowel includes intubation of the complete colon and mucosal visualization. The investigators demonstrate that terminal ilium intubation is possible in endoscopy practice and yields additional clinical details. Furthermore, it may be used as an indicator of colonoscopy completion.Objectives: This study estimated the rate of cecal and ilial intubation by a single well-trained endoscopist and compared it with the results of a heterogeneous group of endoscopists.Patients and Methods: This retrospective comparative study estimates the rate of cecal and ilial intubation in a private endoscopy center in which all the endoscopic procedures were conducted by a single consultant gastroenterologist, and compared it with the rates of a governmental center with by five colonoscopy endoscopists (general surgeons, general physicians, trained endoscopists, and gastroenterologists). The study population included 442 patients (245 males [55.42%] and 197 females [44.58%], ranging from 14 to 85 years of age.Results: Overall cecal and ilial intubation rates were 88% and 47.5%, respectively. The adjusted rates for cecal and ilial intubations were 94.2% and 50.8%, respectively, after considering cases of anatomic colonic obstruction and when the clinical indications do not justify total colonic intubation. These figures were superior in comparison to the results of a multi-operator study in which the cecal- and the ilial intubationrates were 51.81% and 30.69%, respectively.Conclusion: Cecal and ilial intubation are important quality indicators for colonoscopy, and in this study, they were found to be superior in qualified gastroenterologists than in general surgeons and physicians. This outcome points to the importance of providing endoscopy units in Iraq, with qualified well-trained endoscopy personnel.